Analysis of Advocates' Speaking Strategies in Criminal Case Defense: Its Implementation and Challenges - Minto, Deri Wan; Anshori, Dadang S.; Damaianti, Vismaia S.; Sastromiharjo, Andoyo; Putriani, Ananda (UNIB Press, 2024)
This research was conducted due to the importance of speaking strategies that advocates in court should possess. This study aims to describe the advocate’s speaking strategies in court, seen from the plea and exception drafts, and to see how they can be implemented in advocate professional education in Indonesia. The type of this research is qualitative descriptive using a descriptive analysis approach. The data are plea and exception drafts, notes, and court minutes. The data were collected through observation, interviews, recording, and collecting the the collection of plea and exception drafts. The validity of the data was assured by using semantic validity. The data was analyzed by reducing and presenting the data and drawing conclusions. The results showed that the speaking strategy used mainly by the advocate at the trial was straightforward speaking strategies with positive politeness pleasantries, which was 52.6%. Meanwhile, the lowest number of speaking strategies found in the draft were straightforward speaking strategies without any form of pleasantries, and it was 9.1%. Based on these data, the concept of a speaking strategy has been implemented, although there are still various obstacles and shortcomings. The challenges that arise include advances in technological development, mastery of the concept of speaking strategies, and digital-based learning components. Involvement and engagement with various elements are helpful for the advancement of professional training of prospective advocates in order to achieve the vision, mission, and expected goals.